The Phenomenon of Increasing Political Participation in the 2020 Major Election of Semarang with One Candidate Pair in Political Marketing Perspective - Henry Casandra Gultom; I Made Bayu Dirgantara (Budapest International Research and Critics University, 2022)
The election of the Mayor and Deputy Mayor (Pilwakot) of Semarang with a single candidate pair is a first in the history of the Semarang Election. Public involvement in the Semarang City Elections has increased dramatically as a result of the Pandemic-Covid-19 crisis. The goal of this qualitative study, which includes phenomenological studies, is to identify the elements that contribute to increased political engagement in Semarang. Data was acquired through observation, interviews, and documentation. The phenomena of increased political engagement in the 2020 Semarang Elections is affected by digital media-based information marketing, according to this study. Second, the Semarang’s General Comission Election (KPU) discusses various digital media-based political marketing methods. Third, the Semarang KPU employs long-term digital information marketing to raise voter and prospective voter knowledge about the next general election's implementation.